Religions in National Integration . A Gandhian Perspective - Chirappanath, Antony (Journal of Dharma, 1983)
Can religion play any role in the process of National Integration? What is the testimony of history with regard to this? What has usually happened at the birth of any new religion ? Is there any religion which has not caused division, dissension, discord and even bloodshed in society some time or the other ? It appears that religion has always been a disintegrating factor in society. It continues to be so. And we do not see any reason why it to be any different in the future. Whether it should continue to be so in the future one does not know. Certainly it need not be so if religion is properly understood. But how is this possible ? When there are conflicting elements in different religions, how can they bring about unity, harmony or integration.